P Produk Asuransi Syariah di Indonesia: Prospek dan Tantangan: Produk Asuransi Syariah di Indonesia: Prospek dan Tantangan - Nico Hadi; Yulfiswandi; Alexander; Shinta Dewi; Vivi Sonata; Jeslin (Politeknik Kutaraja, 2023)
The purpose of this study is to be able to analyze the prospects and challenges of Sharia Insurance products in Indonesia, as well as get a broader view of Sharia Insurance and be able to deepen understanding of the prospects and challenges of Sharia Insurance products in Indonesia. This research method is qualitative with data collection techniques, namely literature study, and observation by visiting the official website of the Otoritas Jasa Keuangan (OJK) to obtain relevant data. Indonesia has a society that is predominantly Muslim so it has a large market share and opportunity. However, this does not fully make people interested in using Sharia Insurance products so that it becomes a challenge in the development of Sharia Insurance products in Indonesia. Some of the challenges faced by Sharia Insurance products are starting from the lack of professional human resources, the absence of comprehensive information dissemination and the lack of public awareness of insurance. Keywords: Islamic insurance products, Prospects, Challenges, Sharia Insurance